Bixa orellana (achiote) hydroalcoholic liofilized leaves effect on rats’ gastric secretion - Huamán, Oscar (2007)
Objective: To determine the effect of Bixa orellana (achiote) leaves hydroalcoholic extract on non-protein sulphydryles groups (NP-SG), gastric mucus pH and gastric secretion total acidity. Design: Prospective, analytical-experimental and transversal study. Setting: Biochemistry and Nutrition Research Centre, Faculty of Medicine, Universidad Nacional Mayor de San Marcos. Biologic material: To determine the effect of the extract on gastric mucosa we used the pyloric ligation model proposed by Vissher and modified by Sandoval. For NPSG determination Sadlak and Lindsay method was used, Corne’s method for gastric mucus production, pH and total acidity potentiometer by titration with NaOH. Main outcome measures: Levels of sulphydryle non-protein groups (NP-SG), gastric mucus, pH and total acidity. Results: Bixa orellana leaves hydroalcoholic extract NP-SG increased in 133% and 168% (p <0,01) at 100 and 200 mg/kg doses and increased mucus production in 39,4% and 44,9% respectively at 200 and 400 mg/kg doses (p<0,01). Only in the group receiving the 400 mg/ kg dose there was a significant pH decrease (p<0,05). On the other hand, at 100, 200 and 400 mg/kg extract doses total acidity increased 62,3%, 58,2% and 166,6% respectively (p<0,01). Conclusions: Treatment with Bixa orellana leaves extract increases the production of mucus and GS-NP but does not inhibit total acidity.